Playing Plasticine to Develop Social Emotional of 5-6 Years Old Children - Salma Zahrani Putri; Rista Sundari (Al Hikmah Indonesian Journal of Early Childhood Islamic Education, 2025)
Both aspects of social and emotional development the relationship to one another. It is impossible to ignore the social aspect when talking about emotional development, and vice versa. When discussing social development, emotional elements are always involved. These two aspects are important components of psychology. At the Islamic Kindergarten Satria Hasanudin, this study aims to conclude how playing with modeling clay can develop children's social and emotional skills. The study uses a qualitative method with a case study approach through interviews, observations, and documentation. The children from group B at Islamic Kindergarten Satria Hasanudin, totaling 22 students, are the subjects of this research. By engaging in this activity, students can enhance their sense of empathy, cooperation, create an active classroom atmosphere, and foster care which is closely related to social and emotional aspects. The findings from this study can have a positive impact on the development of children's social and emotional skills, which can be utilized as an effective type of play to develop emotional regulation and enhance feelings of social concern. Therefore, this activity is recommended to be integrated into the learning process in early childhood education settings.